What Influences Parenting Behaviour? The Role of Parent Self-Concept. Issue 4 (25th December 2020) - Gittins, Catherine B.; Abbott, Maree J.; Hunt, Caroline
Abstract: Parenting has a strong influence on child development. However, there is minimal empirical evidence on why some parents use beneficial techniques, while others use harmful behaviours. Thus, there is a significant gap in the knowledge needed to address problematic parenting. Theories suggest that parental self-concept has a large influence on parenting behaviours. The aim of this study was to examine the relation between parent self-cognitions and parenting behaviours. One-hundred and four mothers of Grade 7 students completed questionnaires measuring their self-esteem, self-criticism, domain-specific self-concept, and parenting behaviours (support, behavioural control, and psychological control). Regression analyses demonstrated that self-cognitions largely predicted psychological control but support or behavioural control did not. These findings suggest that psychologically controlling behaviour in parents may be due to poor self-worth. With psychological control known to deeply damage children, these findings have major implications for interventions targeting harmful parenting.